Influence of the site of oviposition on the level of egg parasitism in the corn leafhopper, dalbulus maidis (Hemiptera: Cicadellidae) - Luft Albarracin, Erica Beatriz (2021)
The corn leafhopper Dalbulus maidis (DeLong) (Hemiptera: Cicadellidae), transmits three important plant pathogens that adversely affect corn crop and ranges from the USA to Argentina. The vector has a rich natural enemy complex that generates high levels of parasitism, but its populations are persistent and prevalent. We characterized the oviposition sites of D. maidis on young corn plants in order to verify the hypothesis that the vector has an oviposition strategy for mitigating parasitism. Oviposition locations on plants were assessed in the laboratory and eggs within corn plants were exposed to natural parasitism in a cornfield. Eggs were located mostly laid in the unfolded leaves and were attacked by five parasitoid species. Parasitism was significantly affected by the class of leaf and the position of the egg in the leaf. Anagrus virlai Triapitsyn was the most abundant parasitoid species, which emerged significantly higher in the basal blade than other species. Our results suggest that leafhoppers minimize egg parasitism by laying their eggs within concealed locations on the plant.